Point of care testing of Influenza A/B and RSV in an adult respiratory assessment unit is associated with improvement in isolation practices and reduction in hospital length of stay. Issue 5 (6th April 2020) - Berry, Louise; Lansbury, Louise; Gale, Lydia; Carroll, Ann Marie; Lim, Wei Shen
Abstract : Introduction. Every winter seasonal influenza and other viral respiratory infections increase pressure on the health services and are associated with nosocomial infection and morbidity. Aim. To compare provision of point-of-care (POC) testing with laboratory-based testing for influenza and RSV detection on an adult respiratory assessment unit to assess the impact on isolation practices and length of stay (LOS). Methodology. Prospective interrupted 'on-off' study in adults admitted to the respiratory unit between December 2018 and April 2019 with a suspected respiratory tract infection. Nasopharyngeal samples were tested using either the GeneXpert rapid POC test for influenza and RSV (on-period), or were sent to the laboratory for multiplex PCR testing against a panel of 12 respiratory viruses (off-period). Outcome measures were time to patient isolation for infection control, LOS and turnaround time from admission to test results. Results. Of 1145 patients evaluated, 755 were tested with POC and 390 with laboratory multiplex; a respiratory virus was identified in 164 (21.7 %) and 138 (35.4 %) patients respectively. A positive POC test was associated with a shorter time to isolation (mean difference 16.9 h, P <0.001), shorter LOS (mean difference 15.5 h, P =0.05, ) and shorter turnaround time (mean difference 28.3 h, P <0.001), compared to laboratory testing. Conclusion. Use of GeneXpert POC testing for Flu/RSV is associated with rapid reporting of results with significant improvements in isolation practices and reductions in LOS.